Whistleblowing toward a new theory - Kenny, Kate (Kate Marguerite) (Harvard University Press, 2019)
When people try to speak up about serious wrongdoing in their organizations, they are often ignored and sometimes punished for their efforts. Society tends to accept the suffering of whistleblowers, who often experience significant retaliation, as more or less normal. This book challenges this acceptance. It explores how the narrative might be changed. Whistleblowing draws on emergent theories in the fields of organization studies and sociology to address the questions of why whistleblowers are frequently ignored and why, if they are acknowledged for speaking up, they are then isolated by colleagues, industry peers, and even loved ones. Kate Kenny offers a new way to understand whistleblowing and the experiences of those involved in it, and explains both how whistleblowers can cope and survive their ordeal and how organizations can change to protect and benefit from whistleblowers.--